2000
DOI: 10.1021/jp002257p
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure at Organic/Metal Interfaces:  Naphthalene/Cu(111)

Abstract: Electron transfer at organic/metal interfaces is a fundamental issue of interest to a large number of problems in chemistry. We use two-photon photoemission (2PPE) spectroscopy to investigate heterogeneous electron transport in a model system: naphthalene adsorbed on Cu(111). The dependence of 2PPE spectra on photon energy establishes the occurance of photoinduced electron transfer to an unoccupied state at 3.1 eV above the Fermi level (or 1.1 eV below the vacuum level) at one monolayer coverage. Polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
71
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 46 publications
18
71
0
Order By: Relevance
“…Presumably, the first maximum at $204 K is due to the multilayer desorption (peak a), while the second maximum centered at $218 K could be attributed to desorption of a more strongly bounded bilayer species (peak b 2 ). This observation is in agreement with the previous study of naphthalene adsorption on the Cu(1 1 1) surface where the authors found the formation of a second layer which desorbs at a temperature slightly higher than the multilayer desorption [15]. A feature at $190 K for the highest exposure (25 L) is also observed (see the star in Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Presumably, the first maximum at $204 K is due to the multilayer desorption (peak a), while the second maximum centered at $218 K could be attributed to desorption of a more strongly bounded bilayer species (peak b 2 ). This observation is in agreement with the previous study of naphthalene adsorption on the Cu(1 1 1) surface where the authors found the formation of a second layer which desorbs at a temperature slightly higher than the multilayer desorption [15]. A feature at $190 K for the highest exposure (25 L) is also observed (see the star in Fig.…”
Section: Resultssupporting
confidence: 93%
“…Naphthalene has been studied in the gas phase as well as in the solid state by both experimental and theoretical methods [6][7][8][9]. As a fundamental p-conjugated model system, naphthalene adsorption on different substrates has attracted much attention [10][11][12][13][14][15][16][17][18]. Naphtalene on Pt(1 1 1) has been investigated by means of low-energy electron diffraction (LEED) [10][11][12], Auger electron spectroscopy and work-function measurements [10], and scanning tunneling microscopy (STM) [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of adsorbates that do not introduce unoccupied electronic levels in the energy range of the image-potential states, the wave functions of the latter will retain their simple hydrogenic character, but will be repelled from the metal. Systems with such properties that have been studied by time-resolved 2PPE include Xe/Ag(1 1 1) [258,259], alkanes/Ag(1 1 1) [260,261], Xe/Cu(1 1 1) [262,263], O 2 /Xe/ Cu(1 1 1) [264], N 2 /Cu(1 1 1) [263], N 2 /Xe/Cu(1 1 1) [263], naphthalene/Cu(1 1 1) [265], Xe/ Ru(0 0 0 1) [266,267] and Ar/Cu(1 0 0) [268,269]. Data obtained for the two latter systems are shown as examples in Figs.…”
Section: Decoupling By Spacer Layersmentioning
confidence: 99%
“…The molecules interact with the metal in several ways (see Fig. 2), i.e., metal polarization (e.g., tris-(hydroxyquinoline)Al (Alq) on Ag, [15] or naphthalene on Cu [26] ), coupling of electronic states (e.g., C 6 F 5 S ± on Cu [14] ), partial charge exchange (ionic bond formation by thiophene on Al [27] ), or even formation of new chemical species by covalent bond formation, (organometallic complex formation of Alq on Mg [28] ). The importance of metal±molecule interactions is also clear from the inversion of dipole direction upon adsorption of benzoic acids on indium tin oxide (ITO) or on Al.…”
Section: Metal±molecule Contactsmentioning
confidence: 99%